Heterogeneity of sediments and settling particles in aerated ponds - Kassila, Jawad; Hussenot, Jerome (Aquaculture Research, 2006)
A study was conducted in seabass (Dicentrarchus labrax) and oyster (Crassostrea gigas) ponds to assess the levels of heterogeneity of sediments and settling particles. The intensity of sampling to estimate with high accuracy some characteristics will depend on the magnitude of the variation within the population under consideration. Several variables, such as total phosphate (Tot-P), total iron (Tot-Fe), total ammonium nitrogen (TAN), organic carbon (Org-C), total nitrogen (Tot-N) and P fractions were analysed during the rearing period. The box-and-whisker plots were used as graphical/statistical tools to visualize the descriptive statistical characteristics of the data. In the fish pond, the sediments have high concentrations of Tot-P, Tot-Fe and TAN in comparison with the settling particles. The high C/N ratios in the sediments indicate that the organic matter was more highly degraded in comparison with that of settling particles. The iron- and calcium-bound P (CaCO3 approximate to P) represented 23% and 47% of Tot-P respectively in the fish-pond sediments, whereas the Tot-P was essentially under organic form in the settling particles. In the oyster pond, the trapping rate of solids reached 417 g m(-2) day(-1) under the trestles. The material consisting mostly of oyster rejection products was less degraded. The similarity in the C/N ratios indicated that the organic matter collected under the oyster trestles was not different from that collected out of trestles. We used multivariate analysis to determine the number of samples needed to be taken to represent the C, N and P average amounts. The principal component analysis (PCA) indicates that the CaCO3 approximate to P and Tot-Fe are the key factors to describe the spatial heterogeneity of the fish-pond sediments. However, the analysis gives no indication of the heterogeneity of settling particles. A partition of the studied stations into different classes was performed by the hierarchical ascending classification (HAC). To assess the variability of the ...